Staphylococcal Infections Recent Advances and Perspectives - Bustos-Martínez, Jaime; José Valdez-Alarcón, Juan (Infectious Diseases, 2023)
The study of staphylococci has a long way to go, due to the great significance both for humans and for dairy or companion animals of their large number of virulence factors. Their resistance to antibiotics makes these microorganisms become highly pathogenic species that can cause infections ranging from mild to fatal. Staphylococci, especially S. aureus and strains resistant to methicillin (MRSA), are among the most studied microorganisms worldwide. This book covers recent advances in the study of staphylococci. The book is divided into four sections that cover four important events for the study and combat of staphylococci: colonization, epidemiology and pathogenesis, diagnosis, and new treatments. Staphylococci can present a broad spectrum of resistance to antibiotics, which is why their elimination has become difficult. The final section of the book is devoted to new compounds for the fight against staphylococci. We hope that the information contained in this book will be useful for the study and investigation of these medically important microorganisms.